Binary and ternary complexes of FLNa-Ig21 with cytosolic tails of αMß2 integrin reveal dual role of filamin mediated regulation - Zhiping, Lewis Lu; Ong, Li-Teng; Chatterjee, Deepak; Tan, Suet-Mien; Bhattacharjya, Surajit (Biochimica et biophysica acta. General subjects, 2021)
Cytoskeletal protein filamin A is critical for the outside-in signaling of integrins. Although molecular mechanisms of filamin-integrin interactions are not fully understood. Mostly, the membrane distal (MD) part of the cytosolic tail (CT) of β subunit of integrin is known to interact with filamin A domain 21 (FLNa-Ig2). However, binary and ternary complexes of full-length CTs of leucocyte specific ß2 integrins with FLNa-Ig21 are yet to be elucidated. Binding interactions of the CTs of integrin αMß2 with FLNa-Ig21 are extensively investigated by NMR, ITC, cell-based functional assays and computational docking. The αM CT demonstrates interactions with FLNa-Ig21 forming a binary complex. Filamin/αM interface is mediated by sidechain-sidechain interactions among non-polar and aromatic residues involving MP helix of αM and the canonical CD face of FLNa-Ig21. Functional assays delineated an interfacial residue Y1137 of αM CT is critical for in-cell binding to FLNa-Ig2. In addition, full-length ß2 CT occupies two distinct binding sites in complex with FLNa-Ig21. A ternary complex of FLNa-Ig21 with CTs has been characterized. In the ternary complex, αM CT moves away to a distal site of FLNa-Ig21 with fewer interactions. Our findings demonstrate a plausible dual role of filamin in integrin regulation. The molecular interactions of the ternary complex are critical for the resting state of integrins whereas stable FLNa-Ig21/αM CT binary complex perhaps be required for the activated state. Filamin binding to both α and β CTs of other integrins could be essential in regulating bidirectional signaling mechanisms. [Display omitted] •Filamin A is known to maintain the inactive state of integrins including αMβ2.•Filamin A (FLNa-Ig21) binds to full-length cytosolic tail (CT) of β2 integrin.•The α CT of αMβ2 integrin demonstrates novel binding to the CD face of FLNa-Ig21.•FLNa-Ig21/αM CT complex occurs in activated integrin.•FLNa-Ig21/αMβ2 CTs ternary complex stabilizes inactive state of αMβ2 integrin.